2019
DOI: 10.3345/kjp.2018.07066
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus-associated seizures in Korean children, 2011–2016

Abstract: Purpose Respiratory syncytial virus (RSV) infection can cause various neurological complications. This study aimed to investigate the RSV-associated neurologic manifestations that present with seizures. Methods We retrospectively reviewed the medical records of patients aged less than 15 years with laboratory-confirmed RSV infections and seizures between January 2011 and December 2016 in a regional hospital in South Korea. Results During this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 29 publications
0
27
0
2
Order By: Relevance
“…A Taiwanese study 28 showed that systematic infection was an independent risk factor for epileptic seizures, conferring a 10.7-fold higher risk compared with the control group. In addition, human herpesvirus 6 (HHV-6), 29 Epstein-Barr virus (EBV), 29,30 respiratory syncytial virus infections, 31 and urinary tract infections 32 could increase epilepsy risk. The prognosis of infection-related epilepsy was poor, and the hospital mortality rate was 16%.…”
Section: Infectious Diseases and Epilepsymentioning
confidence: 99%
“…A Taiwanese study 28 showed that systematic infection was an independent risk factor for epileptic seizures, conferring a 10.7-fold higher risk compared with the control group. In addition, human herpesvirus 6 (HHV-6), 29 Epstein-Barr virus (EBV), 29,30 respiratory syncytial virus infections, 31 and urinary tract infections 32 could increase epilepsy risk. The prognosis of infection-related epilepsy was poor, and the hospital mortality rate was 16%.…”
Section: Infectious Diseases and Epilepsymentioning
confidence: 99%
“…Furthermore, when infection-related epilepsy in children is not well cured, the in-hospital mortality rate could reach 16%. 30 Children tend to be the main targets of human herpesvirus-6 (HHV-6), Epstein-Barr virus, 31 , 32 central nervous system infection, respiratory syncytial virus infection 33 and urinary tract infection, 34 which all may increase the risk of epilepsy. Accordingly, in children with a history of epilepsy or a family history, special attention should be paid to the prevention of infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Both, in humans and animal models it has been observed that after exposure to hRSV, disease manifestations can involve the CNS ( Millichap and Wainwright, 2009 , Picone et al, 2019 , Espinoza et al, 2013 ). Indeed, a proportion of patients with hRSV-associated severe bronchiolitis can develop neurological abnormalities, such as seizures ( Kho et al, 2004 , Ng et al, 2001 , Cha et al, 2019 ), central apnea ( Kho et al, 2004 ); lethargy, ( Sweetman et al, 2005 , Kho et al, 2004 ) feeding or swallowing difficulties ( Sweetman et al, 2005 , Kho et al, 2004 ), strabismus ( Antonucci and Fanos, 2005 ), encephalopathy ( Eisenhut, 2007 , Millichap and Wainwright, 2009 , Picone et al, 2019 , Bohmwald et al, 2014 , Bohmwald et al, 2018 ), and elevated cytokines levels or increased cellularity in the cerebrospinal fluid (CSF) ( Kawashima et al, 2012 , Kho et al, 2004 , Otake et al, 2007 ). Additionally, studies in rodents have shown that hRSV can cause cognitive alterations, similarly to what has been reported for the other respiratory viruses, such as the influenza virus and SARS-CoV-2 ( Jurgens et al, 2012 , Jang et al, 2009 , Mao et al, 2020 , Meinhardt, 2020 , Moriguchi et al, 2020 , Bernard-Valnet, 2020 , Hornuss, 2020 , Rogers et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%